(3GdCYdGb GdNWjQI aj JGQjN GdTGe hGdLRjQIs - (3eMeO Hf EHQGgje Hf TOGO YR GdOjf GdCfUGQj GdcGJH GdMdHj, CHh Ydj,J (B684 (3g` s
(3ChdgG (B:s
(3jbhd GdYHO GdabjQ Edi Gddg JYGdi GdZfi Hg eMeO Hf Ydi Hf TOGO hHYO aEfg deG MdJ HeUQ GdeMQhSI hJHhGJ GdeGfhSI hSdefi ef GfYGe ehdGfG GdSdWGf s
(3BNQgG (B:s
(3RGf Gddg jeSc GdSehGJ hGdCQV Cf JRhdG Gddge eeSc GdSehGJ hGdCQV (B) s
(3fSNI KGfjI UhQJ Yf fSNI GdeQMhe GdTjN fGLi GdcQOi bje GdLGeY GdCehi HMdHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe LRA (B2/ 1 - (3U (B20 s
Keywords: (3GdJGQjNs